Understanding the perspective of community co-educators on community-based service learning: A qualitative analysis - Zhou, Grace; Thayaparan, Aarabi; Park, Stephanie; Sadeghi, Yasamin; Deimling, Brandi; Wright, Roxanne; Leung, Fok-Han (Canadian Medical Education Journal / Revue canadienne de l'éducation médicale)

(untitled) (Canadian Medical Education Journal, 2024)
Background: Community-based service learning (CBSL) is a core component of the Canadian medical education system. However, the unique role of community partner organizations (CPOs) in supporting CBSL remains unclear. This qualitative study evaluates the perspective of CPOs as co-educators in the undergraduate medical curriculum.Methods: We conducted eight semi-structured, one-on-one interviews with CPOs at a medical school in Toronto, Ontario between 2020-2021. Interviews were conducted following a pre-determined interview guide and then recorded, de-identified, and transcribed. Three reviewers independently performed an inductive thematic analysis of codes followed by a group review of discrepancies.Results: Five main findings were identified: 1) CPOs share a common interest in serving as co-educators; 2) considerable heterogeneity in the understanding of co-education exists; 3) there is an opportunity for increased partnerships between CPOs and faculty; 4) the role of co-educators is limited by curriculum structure; and 5) co-educators facilitate unique teachings of social determinants of health otherwise not available through traditional didactic teaching.Conclusions: There is an emerging, unique role for community co-educators in the undergraduate medical curriculum, supported by interest from CPOs. Its emphasis may contribute to future cohorts of medical students capable of understanding and addressing the needs of the populations they serve.